Agama di Tengah-tengah Perubahan Masyarakat - S Sukirdi (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
Changes in society that covers all aspects of society can be occurred either naturally or artificial. The changing process is taking place throughout the history of human life locally, nationally and regionally. This illustrates how wide is the scope of the study of society. Due to the fact that changes in society brings the impact, either positive or negative, religion is needed in society as a counterweight and as a filter for negative impacts that might be occurred.